Ultrasonographic and histopathological investigation of the effect of N-acetylcysteine on doxorubicin-induced ovarian and uterine toxicity in rats - Evren Üstüner; Ebru Yıldırım; Hasan Ceyhun Macun; Hüsamettin Ekici; Yaşar Şahin; Enes Güncüm; Tuğçe Anteplioğlu; Taha Burak Elifoğlu; Esra Bozkaya (BMC, 2024)
Abstract Background This study aimed to investigate the mitigating effect of N-acetylcysteine (NAC) on doxorubicin (DOX)-induced ovarian and uterine toxicity in rats using laboratory tests, ultrasonographic (US) imaging, and histopathology analysis. Methods Forty-eight rats were divided into six groups (n = 8) as follows: Group A (control) (0.5 mL saline administered intraperitoneally [IP]), Group B (a single 10 mg/kg dose of DOX administered IP on day 1), Group C (a single 10 mg/kg dose of DOX administered IP 24 h before sacrifice), Group D (100 mg/kg of NAC administered IP for 21 days), Group E ( a single 10 mg/kg dose of DOX administered IP on day 1 and 100 mg/kg of NAC administered IP for 21 days), and Group F (100 mg/kg of NAC administered IP for 21 days and a single 10 mg/kg dose of DOX administered IP 24 h before sacrifice). The ovaries were examined using B-mode US on days 1, 14, and 21, and the histopathological examinations of the ovaries and the uterus were undertaken after sacrifice on day 22. Results Histomorphological analyses showed that ovarian weight decreased after DOX administration in Group B but not in Group E. US revealed a transient increase in ovarian size in Group B and E, reverting to baseline levels over time, as well as a progressive increase in peritoneal fluid in Groups B and E. Group B exhibited a significant decrease in the thickness of the endometrium and myometrium and uterine cornual length, which was not observed in Group E. Histopathological examination showed that DOX caused a decline in follicular count, especially in primordial, secondary, and Graafian follicles, and resulted in follicular atresia, predominantly in Group B. Destructive degeneration/necrosis and vascular changes were most prominently seen in the corpus luteum of Groups C and B. In NAC-treated rats (Groups E and F), although germ cell damage was present, atretic follicles and vascular changes, such as hyperemia and congestion, were reduced. The anti-müllerian hormone (AMH) level was the highest in Group F. Conclusions NAC, an antioxidant, attenuated DOX-induced gonadotoxicity in rats.